Assessment of knowledge of hypertension and its risk factors among urban school children of Belagavi: a cross sectional study - Gunagi, Praveena; Harikanth, Disha Rama (International Journal Of Community Medicine And Public Health, 2023)
Background: Hypertension has not just remained the disease of adults, but the prevalence is also increasing in children and adolescents. Knowledge of the predisposing risk factors of hypertension is an important step in the modification of lifestyle behaviours to prevent further morbidity and mortality. Methods: This cross sectional study was conducted among 270 students of 10th standard, belonging to 3 urban schools of Belagavi in 2016 using a structured questionnaire with an intention to assess their knowledge regarding hypertension and its risk factors. Results: Majority students (69.26%) belonged to class II and III of B.G Prasad socio-economic status and 70.37% came from nuclear family. While headache (80%) was the most answered symptom, heart diseases (67%) was the commonly answered complication. Most students had good knowledge regarding prevention and risk factors like unhealthy diet, physical inactivity etc. Majority had fair knowledge about general factors (54.81%), symptoms (41.11%) and complications (34.11%). Knowledge about stress factors (46.67%) and preventive measures (62.22%) was very good. All these differences were statistically significant (p<0.001). Conclusions: The overall knowledge about hypertension and its risk factors among the school students was good (68.52%) and there was significant association between the overall knowledge levels with the mothers education and family history of chronic diseases.